PENANAMAN AKHLAK DALAM PEMBELAJARAN BERDASARKAN GAYA KOMUNIKASI GURU - Basalama, Bismar; Jumari; Surur, Shobihus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2020)
Education in Indonesia in addition to developing cognitive abilities also emphasizes the moral development of students. To support students' moral development in learning, one of which is the quality of teacher communication. Young teachers with little experience but has advantages in terms of energy and stamina are expected to be able to realize learning that instills morals. For this reason, the authors conducted a study of learning in moral cultivation by young teachers based on communication styles at MTs / SMP Jombang. The study includes: how is the concept of moral cultivation in learning based on communication styles? how is the strategy for moral cultivation in learning based on communication styles? what are the implications of moral cultivation in learning basedon communication styles? This study uses library research (library research) and field (field research). The data collection process includes literature study and field studies (observations and interviews). The research instrument used is written sources in the form of books and scientific journals. observation sheets (Communication Style, RPP, Learning in Cultivating Student's Morals), recording tools, and interview guides. The stages of data analysis include (1) transcribing data; (2) coding the data; (3) checking the validity of the data or triangulating data; (4) analyzing the data; (5) drawing conclusions. Based on the literature study, the concept of moral cultivation in learning based on communication styles can be done by adjusting students 'thinking skills and cultivating their morals by means of Taqlid, (Imitation), Tajribah wa Khata' (Exercise), Ta'wid (Habit). The strategy to cultivate morals in learning based on communication styles is classical and non-classical learning and the cultivation of morals by means of Taqlid, (imitation), Tajribah wa Khata '(Exercise), Ta'wid (Habit). The implication of cultivating morals in learning based on communication styles is the installation of morals in students including being devoted to Allah SWT, being grateful to Allah SWT, being honest (As-Sidq), conscientious (Al-Dhabt), hard work (Al-Jidd). responsibility (Al-Amanah) and cooperation (At-Ta'awun).